Outreach and support in south London (OASIS): implementation of a clinical service for prodromal psychosis and the at risk mental state. - Broome, MR; Woolley, J; Johns, L; Valmaggia, L; Tabraham, P; Gafoor, R; Bramon, E; McGuire, P (2005)
BACKGROUND: While recent research points to the potential benefits of clinical intervention before the first episode of psychosis, the logistical feasibility of this is unclear. AIMS: To assess the feasibility of providing a clinical service for people with prodromal symptoms in an inner city area where engagement with mental health services is generally poor. METHOD: Following a period of liaison with local agencies to promote the service, referrals were assessed and managed in a primary care setting. Activity of the service was audited over 30 months. RESULTS: People with prodromal symptoms were referred by a range of community agencies and seen at their local primary care physician practice. Over 30 months, 180 clients were referred; 58 (32.2%) met criteria for an at risk mental state, most of whom (67.2%) had attenuated psychotic symptoms. Almost 30% were excluded due to current or previous psychotic illness, of which two-thirds were in the first episode of psychosis. The socio-demographic composition of the 'at risk' group reflected that of the local population, with an over-representation of clients from an ethnic minority. Over 90% of suitable clients remained engaged with the service after 1 year. CONCLUSION: It is feasible to provide a clinical service for people with prodromal symptoms in a deprived inner city area with a large ethnic minority population.